(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This article examines the organization and transformation of the "Bibiseshanba" and "Bibimushkulkushod" ceremonies, which aim to resolve family issues. The study analyzes changes in their execution, particularly in the Andijan region.